2012
DOI: 10.1038/cr.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

CTCF: from insulators to alternative splicing regulation

Abstract: The zinc-finger DNA-binding protein CTCF has been known for being a constituent of insulators. A recent paper in Nature reports an unforeseen intragenic role for CTCF that links DNA methylation with alternative splicing. By binding to its target DNA site placed within an alternative exon, CTCF creates a roadblock to transcriptional elongation that favors inclusion of the exon into mature mRNA. DNA methylation prevents CTCF binding, which releases pol II transient blockage and promotes exon exclusion.One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…They also demonstrated that the pausing was methylation dependent; when CTCF cannot bind the methylated site, weak exons are not included in the final spliced transcript ( Fig. 2A) (55,56). multiple additional genes have been shown to have promoterproximal CTCF binding (100 bases downstream of the Tss) that results in longer Pol II pausing compared to genes without promoter-proximal binding sites.…”
Section: Direct Splicing Role Of Ctcf Intragenic Binding With Pol IImentioning
confidence: 99%
“…They also demonstrated that the pausing was methylation dependent; when CTCF cannot bind the methylated site, weak exons are not included in the final spliced transcript ( Fig. 2A) (55,56). multiple additional genes have been shown to have promoterproximal CTCF binding (100 bases downstream of the Tss) that results in longer Pol II pausing compared to genes without promoter-proximal binding sites.…”
Section: Direct Splicing Role Of Ctcf Intragenic Binding With Pol IImentioning
confidence: 99%
“…The TF binding landscapes vary in different cell types and genetic contexts (Kasowski et al 2010). Understanding TF binding behaviors is critical to decoding the regulatory mechanisms underlying transcription processes and diseases (Shilatifard et al 2003; Thomas and Chiang 2006;Hawkins et al 2011;Kornblihtt 2012;Yin et al 2017). Chromatin immunoprecipitation followed by DNA sequencing (ChIP-seq) is a widely used method for detecting genome-wide in vivo TF binding profiles (Johnson et al 2007;Kulakovskiy et al 2010).…”
mentioning
confidence: 99%
“…Insulator sequences typically lie within intergenic regions and prevent runaway transcription across neighboring genes, through association with CCCTC-binding factor (CTCF) (13). The role of CTCF has been described in the regulation of alternative splicing (14), as well as through association of DNA methylation at CTCF binding sites, in the generation of alternative splice variants (15). Here, the authors show that CTCF binds to the two insulators and this binding is attenuated upon androgen treatment.…”
mentioning
confidence: 99%